Exercise-mimicking effects of betaine in chronic disease prevention and management - Xu, Yuhui; Gao, Jianhong; Wang, Minghui; Zhang, Hu (Frontiers in Nutrition, 2026)
Betaine, a natural compound found in beets, wheat germ, shellfish, and mammalian tissues, plays a crucial role in preventing and treating various chronic diseases. As the global population ages, chronic diseases are posing the primary threat to the health of the elderly, significantly increasing the medical pressure on families and society. Chronic diseases associated with aging involve complex molecular mechanisms and, therefore, developing multipronged interventions is crucial for their prevention and treatment. Although exercise is a primary intervention for preventing and treating chronic diseases, many elderly individuals have motor disabilities. Therefore, researchers are exploring natural products that mimic the therapeutic effects of exercise in individuals who are unable to exercise. Betaine has exhibited significant preventive and therapeutic effects in studies on chronic diseases and is known as an exercise mimetic. A deeper understanding of betaine may help elucidate crucial molecular mechanisms underlying its effects and offer theoretical insights for developing exercise-mimicking foods, supplements, and drugs, which are expected to benefit the human health.